2017
DOI: 10.5964/ejop.v13i3.1381
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of a parent-training program for promoting cognitive performance in preschool children

Abstract: The study aims to evaluate the effectiveness of a parent training program for promoting cognitive performance of young children through enriching the parent-child interactions among mothers of preschool-aged children in Mashhad, Iran. A total of 29 couples of mothers and their children were assigned to an experimental group (n = 16 couples) and a control group (n = 13 couples). Mothers in the experimental group participated in 12 weekly sessions and were trained how to enrich their daily parent-child interacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 27 publications
(27 reference statements)
0
4
0
Order By: Relevance
“…Tzuriel and Caspi (2017) found that peer mediation and mother-child interaction had significant effects on children’s MLE strategies and CM. Vahidi et al (2017) found that parent-child interactions had a significant effect on preschool children’s cognitive performance. Tzuriel and Shomron (2018) found that mother-child MLE strategies significantly predicted PR and CM of children with LD.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…Tzuriel and Caspi (2017) found that peer mediation and mother-child interaction had significant effects on children’s MLE strategies and CM. Vahidi et al (2017) found that parent-child interactions had a significant effect on preschool children’s cognitive performance. Tzuriel and Shomron (2018) found that mother-child MLE strategies significantly predicted PR and CM of children with LD.…”
Section: Discussionmentioning
confidence: 98%
“…The quantity and quality of mother-child interactions can influence many features of child development, including social, emotional, and cognitive ones (Vahidi et al, 2017). However, in this present world that is rapidly changing and demands that children need to acquire knowledge and many skills to be qualified individuals, many parents are concerned about their children’s cognitive development (Vahidi et al, 2017).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 2 more Smart Citations